Using indocyanine green angiography to achieve complete engraftment of pectoralis major myocutaneous flaps. Issue 5 (May 2023) - Eguchi, T.; Kawaguchi, K; Sato, K; Hamada, Y
Abstract: Although the pectoralis major myocutaneous (PMMC) flap is among the useful reconstructive materials following oral cancer ablation, this flap has an unstable blood circulation that could result in partial necrosis of the skin paddle. This report describes the usefulness of indocyanine green angiography (ICGA) to achieve complete engraftment of the PMMC flap. Five patients with oral cancer underwent reconstruction with a PMMC flap after cancer ablation. During the skin paddle design and flap elevation, the blood supply to the flap was assessed by ICGA. Areas of the skin paddle that showed no ICG fluorescence were excised. Consequently, prior to transfer to the recipient site, the blood supply to all flaps was confirmed with indocyanine green visible at the edge of the skin paddle, and complete engraftment was achieved without partial necrosis. Based on the results observed, ICGA would make a useful contribution to complete engraftment of the PMMC flap.